2020
DOI: 10.2196/14346
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Text Message Contact on Medical Safety in Outpatient Surgery: Retrospective Study

Abstract: Background Establishing pre- and postoperative contact with patients is part of successful medical management in outpatient surgery. In France, this is mostly done via telephone. Automated information with short message service (SMS) reminders might be an interesting alternative to increase the rate of compliance with preoperative instructions, but no study has shown the safety of this approach. Objective The objective of this study was to evaluate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…In this retrospective study, the prevalence of pain on the day after day surgery (318/6099, 5.2%) was similar to that found in a previous study (7%) [ 17 ] but much lower than that reported in the majority of the older studies. In a review published in 2002, the incidence of acute postoperative pain was 45% and ranged from 6% to 95% in 13 studies that included mixed surgical procedures [ 8 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In this retrospective study, the prevalence of pain on the day after day surgery (318/6099, 5.2%) was similar to that found in a previous study (7%) [ 17 ] but much lower than that reported in the majority of the older studies. In a review published in 2002, the incidence of acute postoperative pain was 45% and ranged from 6% to 95% in 13 studies that included mixed surgical procedures [ 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…The emergency consultation or rehospitalization rate found in this study (679/6099, 11.1%) is higher than that reported in our previous work (6.7%) [17] but is comparable to that found by McIsaac et al in 2015 [24], wherein in their population-based cohort of 296,497 outpatients in Canada, 10.5% returned to the emergency unit or were readmitted to hospital within 30 days after the surgery. In another study [18], 2% of 744 patients were admitted to the hospital on an unplanned basis, returned to the hospital, or visited their general practitioner during the postoperative course, but the study was performed on 4 postoperative days only.…”
Section: Xsl • Fosupporting
confidence: 74%
See 3 more Smart Citations